Assessment of liver fibrosis by variable flip angle T1 mapping at 3.0T. Issue 3 (12th August 2015) - Li, Zhiming; Sun, Jihong; Hu, Xi; Huang, Ning; Han, Guocan; Chen, Lumin; Zhou, Yurong; Bai, Weixian; Yang, Xiaoming
Abstract : Purpose: To evaluate the possibility of using a variable flip angle (VFA) T 1 mapping technique to diagnose liver fibrosis. Materials and Methods: Liver fibrosis was induced in rabbits by repetitive administration of carbon tetrachloride (CCl4 ). T 1 ‐weighted magnetic resonance imaging (MRI) was performed in 29 animals (liver fibrosis, n = 18; control, n = 11) using a series of nonenhanced liver acquisition volume acceleration (LAVA) with VFAs at 3.0T. Hepatic T 1 relaxation times were measured via regions of interest, which were correlated with subsequent histologic confirmation. The results of T 1 mapping in assessment of liver fibrosis were compared with that of apparent diffusion coefficient (ADC) values. Results: The mean T 1 relaxation time of the control group was the lowest (250.07 ± 88.12 msec), followed by the nonadvanced fibrosis group (387.83 ± 166.58 msec) and the advanced fibrosis group (496.90 ± 291.24 msec). T 1 relaxation time measurements differed significantly between the liver fibrosis group and control group ( P < 0.05), with a trend of increased mean T 1 relaxation times as the fibrotic stage increased. Statistically significant differences were observed between the control group and the nonadvanced fibrosis group ( P < 0.05), however with much overlap between the less severe stages. In discriminating between the control group and liver fibrosis group, stage F0‐1 (control and stage F1) and stage F2‐3, stage F0‐2 (control and stage F1‐2) and stage F3, area under the receiver operating characteristic (ROC) curves were 0.803 (cutoff value 273.01 msec), 0.712 (cutoff value 371.54 msec), and 0.696 (cutoff value 276.99 msec), respectively. No difference was found between T 1 relaxation times and ADC values in assessment of liver fibrosis in our study. Conclusion: VFA T 1 mapping may become a noninvasive imaging tool for the diagnosis of liver fibrosis. J. MAGN. RESON. IMAGING 2016;43:698–703.